CH4-CO2 mixture behavior at nanoscale: Molecule-wall interactions - Zheng Sun; Chengming Zhao; Zongkai Qi; Liang Ji; Yisheng Liu; Dali Hou; Keliu Wu; Juntai Shi; Dayong Chen (Chemical Engineering Journal, 2026)

Graph-Regularized Point-to-Trajectory Association for RS-AIS fusion toward maritime moving-ship identification and spatial refinement - Xin Du; Ruofei Zhong; Marco Scaioni; Marco Gianinetto; Shiyue Zhang; Qingyang Li; Zhenxing Sun; Chengming Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Engineered extracellular vesicles-fused self-monitoring lipid nanoparticles for targeting activation of specific T cell subsets to enhance cancer immunotherapy - Zhihong Sun; Zijie Yu; Qi Zhao; Cuicui Wang; Bin Li; Sitong Lin; Jie Liu; Chengming Sun; Guanjun Deng; Yong Sun (Chemical Engineering Journal, 2026)

Advancing drought monitoring with a three-dimensional feature space framework - Minghan Cheng; Zhangxin Liu; Jingwen Sun; Linyu Wang; Zhengxian Zhang; Xiuliang Jin; Chengming Sun (Journal of Hydrology, 2026)

Real-Time Monitoring of Anaesthetic-Induced Change of Consciousness States Associated with Brain Biophoton Information Integration - Na Liu; Qiao Wei; Chengming Xia; Jinzhong Li; Chunli Qin; Yan Sun; Zhuo Wang; Hao Lei; Jiapei Dai (Neuroscience Bulletin, 2026)

Using interpretable machine learning method to predict children's fluoride exposure health risks based on routine water quality data: An empirical study in the Huaihe River Basin, China - Kaijun Zhang; Xuedong Sun; Weizhong Wang; Guofeng Yu; Weiqin Meng; Chengming Luo (Journal of Cleaner Production, 2026)

Wheat biomass estimation by fusing color index and canopy volume based on UAV RGB images - Zhaosheng Yao; Dongwei Han; Ruimin Shao; Hainie Zha; Shaolong Zhu; Jianliang Wang; Muhammad Zain; Tao Liu; Fei Wu; Yuanzhi Wang; Chengming Sun (Precision Agriculture, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Mussel protein-graphene hybrid sponge with lung-mimicking architecture for rapid glucose detection - Haohao Shi; Nan Sun; Qikun Li; Dongchen Tan; Sheng Bi; Linguang Li; Shuai Yang; Chengming Jiang (Chemical Engineering Journal, 2026)

Geochemical behavior and environmental implications of Mn(III): Synthesis, redox dynamics, and pollutant removal - Hui Xi; Junzhan Hong; Zhaozhong Zhu; Yunhai Xu; Yingying Sun; Chengming Zhang; Hui Wang; Wendong Wang; Xizi Long (Journal of Water Process Engineering, 2025)

Pre-harvest sprouting in cereals: Global incidence, impacts and mitigation strategies - Rui Yang; Matthew Tom Harrison; Yinmiao Yang; Chunhu Wang; Sergey Shabala; Mingxia Huang; Chenchen Zhao; Meixue Zhou; Chengming Sun; Ke Liu (Field Crops Research, 2025)

Estimation of wheat LAI in different leaf layers through LiDAR canopy vertical light distribution parameters and UAV vegetation indices - Dongwei Han; Shaolong Zhu; Muhammad Zain; Weijun Zhang; Guanshuo Yang; Lili Zhang; Binqian Sun; Yuanyuan Zhao; Zhaosheng Yao; Tao Liu; Chengming Sun (Agricultural and Forest Meteorology, 2025)

Detection of the number of wheat stems using multi-view images from smart glasses - Tao Liu; Jianliang Wang; Junfan Chen; Weijun Zhang; Ying Wang; Yuanyuan Zhao; Yi Sun; Zhaosheng Yao; Jiayi Wang; Chengming Sun (Computers and Electronics in Agriculture, 2025)

ODP: A novel indicator for estimating photosynthetic capacity and yield of maize through UAV hyperspectral images - Shaolong Zhu; Tianle Yang; Dongwei Han; Weijun Zhang; Muhammad Zain; Qiaoqiao Yu; Yuanyuan Zhao; Fei Wu; Zhaosheng Yao; Tao Liu; Chengming Sun (Computers and Electronics in Agriculture, 2025)

Modeling and kinetic analysis for co-pyrolysis of sewage sludge and municipal solid waste under multiple factors - Hongnan Zhang; Yunan Sun; Junyu Tao; Chengming Du; Beibei Yan; Xiangping Li; Guanyi Chen (Environment, Development and Sustainability, 2025)

Combining 2D image and point cloud deep learning to predict wheat above ground biomass - Shaolong Zhu; Weijun Zhang; Tianle Yang; Fei Wu; Yihan Jiang; Guanshuo Yang; Muhammad Zain; Yuanyuan Zhao; Zhaosheng Yao; Tao Liu; Chengming Sun (Precision Agriculture, 2024)

High-throughput identification of fusarium head blight resistance in wheat varieties using field robot-assisted imaging and deep learning techniques - Tao Liu; Yuanyuan Zhao; Yi Sun; Junchan Wang; Zhaosheng Yao; Chen Chen; Xiaochun Zhong; Shengping Liu; Chengming Sun; Tao Li (Journal of Cleaner Production, 2024)

Achieving wheat seedling freezing injury assessment during the seedling stage using Unmanned Ground Vehicle (UGV) and hyperspectral imaging technology - Zhaosheng Yao; Ruimin Shao; Muhammad Zain; Yuanyuan Zhao; Ting Tian; Jianliang Wang; Dingshun Zhang; Tao Liu; Xiaoxin Song; Chengming Sun (European Journal of Agronomy, 2024)

The potential of biomimetic nanoparticles for macrophage repolarisation and phagocytosis in tumour immunotherapy - Zhihong Sun; Rui Zhou; Jie Liu; Qi Zhao; Chengming Sun; Yong Sun (Chemical Engineering Journal, 2024)

APW: An ensemble model for efficient wheat spike counting in unmanned aerial vehicle images - Zhaosheng Yao; Dingshun Zhang; Ting Tian; Muhammad Zain; Weijun Zhang; Tianle Yang; Xiaoxin Song; Shaolong Zhu; Tao Liu; Haijiao Ma; Chengming Sun (Computers and Electronics in Agriculture, 2024)

Environmentally degradable carbon dots for inhibiting P. globosa growth and reducing hemolytic toxin - Hao Li; Chengming Sun; Mengling Zhang; Huibo Wang; Yu Chen; Jun Song (Environmental Pollution, 2024)

Estimation of wheat biomass based on phenological identification and spectral response - Tao Liu; Tianle Yang; Shaolong Zhu; Nana Mou; Weijun Zhang; Wei Wu; Yuanyuan Zhao; Zhaosheng Yao; Jianjun Sun; Chen Chen; Chengming Sun; Zujian Zhang (Computers and Electronics in Agriculture, 2024)

Maize height estimation using combined unmanned aerial vehicle oblique photography and LIDAR canopy dynamic characteristics - Tao Liu; Shaolong Zhu; Tianle Yang; Weijun Zhang; Yang Xu; Kai Zhou; Wei Wu; Yuanyuan Zhao; Zhaosheng Yao; Guanshuo Yang; Ying Wang; Chengming Sun; et al. (Computers and Electronics in Agriculture, 2024)

Dynamic Response Mechanism of Thin-Walled Plate under Confined and Unconfined Blast Loads - Shujian Yao; Yikai Chen; Chengming Sun; Nan Zhao; Zhonggang Wang; Duo Zhang (Journal of Marine Science and Engineering, 2024)
Thin-walled metal plates and cabin structures are widely found in ships and cargos which are susceptible to attacks or accidental explosions. The present work focuses on the dynamic response mechanism of steel plates under unconfined and confined blast loads. In the experiment, digital image correlation (DIC) technique was applied to record and analyze the dynamic response process of a large-scale field blast test. The DIC measured curve and the numerically calculated curves agree well in both trends and peak values. Then, the dynamic response mechanisms of steel plates under an unconfined blast (UB) load and confined blast (CB) load were compared and discussed. The results show that the dynamic response of plates can be divided into three phases under both UB and CB loads, with different mechanisms. In phase I, plastic hinges start from the center and move to the boundary in the UB condition, while in the case of CB, plastic hinges occur close to the boundary and move in the opposite direction. In phase II, two plastic hinge lines propagate towards each other, a platform exists between the boundary, and the central area remains undeformed in the UB condition, while in the CB condition, larger deformation occurs in the peripheral region rather than the central area.

Quantifying key vegetation parameters from Sentinel-3 and MODIS over the eastern Eurasian steppe with a Bayesian geostatistical model - Zhenwang Li; Lei Ding; Beibei Shen; Jiquan Chen; Dawei Xu; Xu Wang; Wei Fang; Alim Pulatov; Maira Kussainova; Amartuvshin Amarjargal; Erkin Isaev; Tao Liu; et al. (Science of The Total Environment, 2024)

Combining vegetation, color, and texture indices with hyperspectral parameters using machine-learning methods to estimate nitrogen concentration in rice stems and leaves - Dunliang Wang; Rui Li; Tao Liu; Shengping Liu; Chengming Sun; Wenshan Guo (Field Crops Research, 2023)

Maternal parity influences the birth sex ratio and birth interval of captive Francois’ langur (Trachypithecus francoisi) - Bojun Yi; Song Wang; Tao Sun; Ruoshuang Liu; Michael J. Lawes; Li Yang; Xuefeng Liu; Yifeng Li; Chengming Huang; Qihai Zhou; Penglai Fan (Behavioral Ecology and Sociobiology, 2023)

How does digital infrastructure break the resource curse of cities? Evidence from a quasi-natural experiment in China - Jingjing Sun; Chenchen Zhai; Xiaoqi Dong; Chengming Li; Zeyu Wang; Dandan Li; Yongping Sun (Resources Policy, 2023)

A novel approach using multispectral imaging for rapid development of seed pellet formulations to mitigate drought stress in alfalfa - Zhicheng Jia; Chengming Ou; Shoujiang Sun; Juan Wang; Jingyu Liu; Manli Li; Shangang Jia; Peisheng Mao (Computers and Electronics in Agriculture, 2023)

High-Performance transparent and flexible Zinc-Ion Solid-State batteries based on nanotube network and hydrogel electrolyte - Nan Sun; Hongjin Sun; Dongchen Tan; Qinglei Guo; Zhe Zhang; Zhiyuan Tao; Chengcheng Fang; Jingyuan Bu; Jijie Huang; Chengming Jiang (Chemical Engineering Journal, 2023)

The estimation of wheat tiller number based on UAV images and gradual change features (GCFs) - Tao Liu; Yuanyuan Zhao; Fei Wu; Junchan Wang; Chen Chen; Yuzhuang Zhou; Chengxin Ju; Zhongyang Huo; Xiaochun Zhong; Shengping Liu; Chengming Sun (Precision Agriculture, 2023)

Small-sized Ni nanoparticles embedded nickel phyllosilicate as a metal-acid bifunctional zeolite catalyst for cooperatively boosting CO2-CH4 reforming - Chengming Huang; Yiming Zhang; Dingmei Han; Binbin He; Xinyu Sun; Meiyu Liu; Yi Mei; Yun Zu (Fuel, 2023)

Development and performance evaluation of TaqMan real-time fluorescence quantitative methylation specific PCR for detecting methylation level of PER2 - Huihui Jiang; Xin Yang; Miaomiao Mi; Xiaonan Wei; Hongyuan Wu; Yu Xin; Liping Jiao; Shengjun Sun; Chengming Sun (Molecular Biology Reports, 2022)

PER2: a potential molecular marker for hematological malignancies - Huihui Jiang; Xin Yang; Miaomiao Mi; Xiaonan Wei; Hongyuan Wu; Yu Xin; Chengming Sun (Molecular Biology Reports, 2021)

Integrating unconditional and conditional QTLs to dissect the genetic basis of stem mechanical strength in Brassica napus L - Kunjiang Yu; Wei Zhang; Yue Guo; Ming Zheng; Feng Chen; Chengming Sun; Maolong Hu; Entang Tian; Xiaodong Wang; Jiefu Zhang (Euphytica, 2021)

Stratigraphic absorption compensation based on multiscale shearlet transform - Chengming Liu; Deli Wang; Jialin Sun; Yibin Li; Fan Yang (Acta Geophysica, 2018)

Closed-loop SRME based on 3D L1-norm sparse inversion - Tiexing Wang; Deli Wang; Jing Sun; Bin Hu; Chengming Liu (Acta Geophysica, 2017)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Automated image-processing for counting seedlings in a wheat field - Tao Liu; Wei Wu; Wen Chen; Chengming Sun; Xinkai Zhu; Wenshan Guo (Precision Agriculture, 2016)

Evaluating the net primary productivity in the grasslands of southern China from 2001 to 2010 using a new land portfolio assessment model - Zhengguo Sun; Chengming Sun; Wei Zhou; Weimin Ju; Jianlong Li (Plant Ecology, 2013)

Sleeping Cave Selection, Activity Pattern and Time Budget of White-Headed Langurs - Chengming Huang; Fuwen Wei; Ming Li; Youbang Li; Ruyong Sun (International Journal of Primatology, 2003)